Green transition of the textile industry: Opportunities and obstacles - Kokeza Gordana; Josipović Sonja (Tekstilna industrija, 2023)
In this paper, the green transition of the textile industry is studied from the point of view of opportunities and obstacles that may arise in this process. In the first part of the paper, the development potential of the green economy concept is studied. In the second part of the paper attention is paid to the experience of EU member states. The third part of the paper is devoted to the study of indicators of the degree of application of the green economy. It is pointed out that green economy indicators represent a grate help in the process of monitoring the success of its implementation at the national level, as well as help in defining effective green policies and green investments. It is concluded that, considering the fact that the textile industry is one of the biggest polluters of the natural environment, there are wide opportunities for applying the principles of green economy in its operations. However, the paper points out that this process is very complex and long-term, as well as that it involves the investment of appropriate resources. Developed countries already apply many of the green economy principles, while undeveloped countries, including Serbia, are only at the beginning of this process.